Walisongo Rodat traditional art as a campaign media to strengthen religious moderation - Alfandi, Muhammad; Warsiyah, Warsiyah (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2024)
This study aims to explore how the traditional art form Rodat Walisongo serves as a medium for promoting religious moderation values. This topic is grounded in the continuing issues of radicalism and the potential for religiously motivated conflict in society, necessitating an intensified campaign for religious moderation through various means, including traditional arts. This research employs a qualitative approach. The primary data source is the Rodat Walisongo traditional art group. Data were collected through observation, interviews, and documentation. The study’s findings reveal that Rodat Walisongo is a medium for promoting religious moderation values through four indicators defined by the Ministry of Religious Affairs. First, strengthening national commitment is demonstrated through Indonesian symbols such as the national flag on costumes and performances, patriotic songs, and Rodat Walisongo songs that convey a spirit of unity. Second, fostering religious tolerance is achieved by creating new songs, including Rukun Ing Ngagomo (Harmony in Religion) and Ngagomo Ora Iso Dipekso (Religion Cannot Be Forced), which embody the principles of interfaith harmony and encourage Muslims to adopt a moderate stance that respects other faiths, reflecting Islam’s message of peace (rahmatan lil 'alamin). Third, the reinforcement of anti-violence values is conveyed through synchronized and harmonious movements in Rodat dance, symbolizing unity, peace, and solidarity. Fourth, local culture is promoted through revitalizing Rodat Walisongo as a valuable cultural heritage that should be preserved and passed on to younger generations. ***** Penelitian ini bertujuan mengungkap bagaimana seni tradisi rodat Walisongo dipergunakan sebagai media untuk mengkampanyekan nilai-nilai moderasi beragama. Ada hal yang mendasari pentingnya kajian ini, yaitu masih adanya radikalisme dan potensi konflik atas nama agama di masyarakat, sehingga dibutuhkan kampanye moderasi beragama yang intensif melalui berbagai media, termasuk melalui media seni tradisional. Penelitian ini menggunakan metode kualitatif. Sumber data penelitian ini adalah group seni tradisi rodat Walisongo. Teknik pengumpulan data melalui observasi, wawancara dan dokumentasi. Hasil penelitian ini yaitu seni tradisi rodat Walisongo dipergunakan sebagai media kampanye nilai-nilai moderasi beragama melalui 4 (empat) indikator moderasi beragama Kementerian Agama, yakni: Pertama, penguatan komitmen kebangsaan, yaitu melalui penggunaan atribut pertunjukan dan seragam dengan bendera Merah Putih sebagai lambang negara Indonesia, serta menyanyikan lagu-lagu perjuangan, maupun lagu-lagu seni rodat Walisongo yang memiliki semangat perjuangan. Kedua, penguatan toleransi beragama, yaitu dengan menciptakan lagu baru yang mengandung unsur-unsur kerukunan antar umat beragama yang berjudul Rukun Ing Ngagomo (rukun dalam beragama) dan Ngagomo Ora Iso Dipekso (beragama tidak dapat dipaksa). Dua lagu tersebut mencerminkan ajaran toleransi beragama yaitu mengajak muslim untuk menjadi umat moderat, yang menghormati dan menghargai penganut agama lain, serta mencerminkan ajaran Islam yang rahmatan lil ‘alamin. Ketiga, penguatan nilai-nilai anti kekerasan, yaitu melalui gerak langkah dalam tari rodat yang memperlihatkan kebersamaan, kekompakan dan kedamaian. Keempat, penguatan budaya lokal, yaitu melalui revitalisasi seni rodat Walisongo, sebagai seni tradisi lokal yang harus dilestarikan keberadaannya dan diwariskan kepada generasi muda.